Demand and supply constraints of credit in smallholder farming: evidence from Ethiopia and Tanzania - Balana, Bedru; Mekonnen, Dawit Kelemework; Haile, Beliyou; Hagos, Fitsum; Yimam, Seid; Ringler, Claudia (Elsevier, 2022)
Credit constraint is often considered as one of the key barriers to the adoption of modern agricultural technologies and low agricultural productivity in low- and middle-income countries. Past research and much of the policy discourse associate agricultural credit constraints with supply-side factors, such as limited access to credit sources or high costs of borrowing. However, demand-side factors, such as risk-aversion and financial illiteracy among borrowers could also affect credit-rationing of smallholder agricultural households. This study investigates the nature of credit constraints, factors affecting credit constraint status, and the effects of credit constraints on adoption and intensity of use of three modern agricultural technologies – small-scale irrigation, chemical fertilizer, and improved seeds. The paper also assesses whether credit constraints are gender-differentiated. Primary survey data were collected from sample farmers in Ethiopia and Tanzania, and Tobit and two-step hurdle econometric models were used to analyze these data. Results show that demand-side credit constraints are as important as supply-side factors in conditioning smallholders’ access to credit in both countries. We also find that credit is a binding constraint for the decision to adopt technologies and input use intensity in Tanzania but not statistically significant in Ethiopia. Results suggest that women are more likely to be credit constrained (from both the supply and demand sides) than men in both study countries. Based on these findings, we suggest that policies should focus on addressing both supply- and demand-side credit constraints to credit access, including through targeted interventions to reduce risk, such as crop insurance, and to strengthen the gender sensitivity of credit policies.